Compet??ncias do l??der de projetos globais de empresas multinacionais brasileiras: uma abordagem contingencial - Teixeira, Laura Ribeiro (2015)
Since the last decades, internationalization is no longer an option, and has become a strategic imperative for all medium and large companies. In this current strategic environment, which is global, technological, interconnected and dynamic, only a few projects are performed exclusively in a country. These projects, which are carried out by combining multiple resources, organizations, cultures and geographies and organizational modes, are called global projects. Global projects differ from domestic projects due to its complexity and challenges involved. In a domestic project, the project leader must be able to manage projects through all project management competence elements and is responsible for managing all aspects of a project, the project leadership roles, application processes, methods, techniques and common project management tools. In a global project, the leader must add to those capacities the capacity to implemente a project in a complex and transcultural environment. To understand the configuration of those capacities, this work focuses on this project leader, or global project manager, and their skills. Through a literature review of the three theoretical axes: international business, project management and skills, and subsequent quantitative study, it was sought to answer the following research question: What are the skills needed for a project leader to manage a global project undertaken by Brazilian multinational companies? Project leaders who managed global projects in Brazilian multinationals were studied, in order to propose a model of project leader skills for the implementation of global projects of Brazilian multinational companies. After statistical analysis of the data, it was found that the core competencies for leading global Brazilian multinational projects are technical and social-emotional skills. With this result, a model was proposed, that highlights which skills should be sought to select the leaders of global projects in Brazilian multinationals.